IMPLEMENTATION OF LOAD BALANCING WITH PER CONNECTION CLASSIFIER AND FAILOVER AND UTILIZATION OF TELEGRAM BOT (CASE STUDY : PT TUJUH MEDIA ANGKASA) - Ariya Pramudita; Rushendra, Rushendra (Jurnal Teknik Informatika (Jutif), 2024)
For customers of PT. Seven Media Angkasa, which is engaged in providing fast online shopping services in Indonesia, definitely needs stable internet to process requests from customers. Even though it already has 2 ISPs, sometimes there are frequent downtimes which will disrupt the service process for customers who want to shop. In this case, one of the Load Balancing methods is the Per Connection Classifier (PCC) which is able to specify a packet to the gateway of a particular connection. Failover for backing up The weakness of the PCC method is Failover which can switch automatically if one of the systems fails so that it becomes a backup for the system that has failed. Added Telegram Bot as a DHCP Alert which can detect if there is a DHCP Rouge. By using the PCC method, it is able to maximize bandwidth usage and minimize the occurrence of downtime in sending or receiving data. So with the addition of the Failover method, if there is a temporary delay when many incoming requests can interfere with performance, Failover can move manually or automatically if one of the systems fails so that it becomes a backup for a failed system. If gateway 1 is disconnected, the backup gateway will replace gateway 1. If gateway 1 returns to normal, the connection path is used again to become gateway 1. Likewise with gateway 2 when it is disconnected. From testing on the speedtest.net tools, it was found that the Load Balancing applied was able to combine 2 ISPs into one, namely Download to 19.18 Mbps and Upload to 18.47 Mbps. The Telegram Bot is able to send notifications when there is a counter DHCP Server with the contents of the message successfully getting a Mac Address or unknown server from the counter DHCP server, namely DC: 2C: 6E: 81: CF: 34.